Pemberdayaan Petani Pumpikatu melalui Penerapan Mina Padi sebagai Upaya Optimalisasi Lahan Sawah - Ashar, Jabal (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Pumpikatu Hamlet, Bulukumba Regency, has considerable potential in rice field areas, yet the management practices remain limited to conventional rice cultivation, resulting in relatively low productivity and farmer income. One promising alternative is the mina padi system, an integrated approach that combines rice cultivation with fish farming in the same field. This system not only improves agricultural output but also provides additional income from aquaculture. This community service program aimed to provide counseling and technical assistance to farmers in Pumpikatu Hamlet in order to enhance their understanding of the mina padi concept, improve cultivation skills, and promote more productive and sustainable land management. The methods included the delivery of extension materials, participatory discussions, technical simulations of land utilization, and direct assistance in the establishment of demonstration plots. The results indicated an increase in farmers’ knowledge regarding the benefits and application of the mina padi system, the development of positive attitudes and motivation to adopt the technology, and the initiation of trial implementation on group-managed rice fields as a demonstration model. Therefore, this program successfully broadened farmers’ perspectives on sustainable agricultural innovations and is expected to contribute to higher land productivity and improved community welfare.